2009
DOI: 10.1258/ijsa.2009.009137
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with unprotected anal intercourse between HIV-positive men and regular male partners in a Sydney cohort

Abstract: Blood plasma HIV-RNA load (BPVL) is the strongest predictor of HIV-1 transmission during sex. Unprotected anal intercourse (UAI) is the highest risk activity for transmission among men who have sex with men (MSM). Awareness of BPVL may influence rates of UAI. We assessed whether optimism towards antiretroviral therapy (ART) and/or biomedical factors influenced sexual activities with regular partners. Questionnaires were administered to 109 HIV-positive MSM participating in a cross-sectional study of BPVL and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Studies have suggested a positive association between condom use in male-to-male anal intercourse and access to HIV preventives actions [19-26]. Our study also found that condom use in the last sexual intercourse were independently associated with HIV infection.…”
Section: Discussionsupporting
confidence: 79%
“…Studies have suggested a positive association between condom use in male-to-male anal intercourse and access to HIV preventives actions [19-26]. Our study also found that condom use in the last sexual intercourse were independently associated with HIV infection.…”
Section: Discussionsupporting
confidence: 79%
“…Failure to find an association was also in contrast with the study’s own finding of an association between beliefs in reduced HIV infectiousness and risk of HIV transmission. The absence of an association between general treatment optimism and HIV risk was also observed in another study among HIV positive MSM from Begley et al [17]. In the study a scale of optimism-scepticism was used to measure treatment-related optimistic beliefs.…”
Section: Resultsmentioning
confidence: 71%
“…A majority (7 out of 10) of the available studies were conducted among HIV positive people [5, 1621]. In addition, there is a heavy concentration of studies (5 out of 10) among men who have sex with men (MSMs) [17, 18, 2224]. The pool of studies also appeared to be dominated by those from developed countries with only two studies from developing countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that peer education activities had a significant impact on sexual behavior at the community level. [32][33][34][35] Peer-implemented education was better accepted, as the messages were more adapted to individuals' needs. Peer-based interventions centered on MSM practices were more adapted to the needs of MSM and offered them a rare chance to have access to lubricants.…”
Section: Discussionmentioning
confidence: 99%